2015
DOI: 10.1017/s136898001500258x
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between height and arm span, mid-upper arm and waist circumferences and sum of four skinfolds in Ellisras rural children aged 8–18 years

Abstract: Objective: Height is required for the assessment of growth and nutritional status, as well as for predictions and standardization of physiological parameters. To determine whether arm span, mid-upper arm and waist circumferences and sum of four skinfolds can be used to predict height, the relationships between these anthropometric variables were assessed among Ellisras rural children aged 8-18 years. Design: The following parameters were measured according to the International Society for the Advancement of Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
(47 reference statements)
0
8
1
Order By: Relevance
“…Wongsodjaja 16 In contrast, South African and Turkish children had longer height than arm span. 22,23 In our study, mean arm span and AHD in females were lower than in males. The mean AHDs in our study were longer than those reported in another Indonesian study (less than 2 cm in both sexes) and in Turkish adolescents (less than 3 cm in both sexes).…”
Section: Discussioncontrasting
confidence: 45%
“…Wongsodjaja 16 In contrast, South African and Turkish children had longer height than arm span. 22,23 In our study, mean arm span and AHD in females were lower than in males. The mean AHDs in our study were longer than those reported in another Indonesian study (less than 2 cm in both sexes) and in Turkish adolescents (less than 3 cm in both sexes).…”
Section: Discussioncontrasting
confidence: 45%
“…The majority of studies were conducted within eight of South Africa's nine provinces (i.e. the country's principal administrative districts); specifically: Eastern Cape (n = 3), 72,75,76 Free State (n = 1), 71 Gauteng (n = 25), 22,26,31,32,[35][36][37]40,46,[48][49][50][51][52][56][57][58][61][62][63]69,[77][78][79][80] KwaZulu -Natal (n = 3), 23,59,60 Limpopo (n = 4), 28,29,81,83 Mpumalanga (n = 8), 44,45,[66][67][68]73,82,86 North West (n = 9) 25,27,30,42,47,64,…”
Section: Resultsmentioning
confidence: 99%
“…51,52,68,83 Sample size ranged between 50 and 3 490 for quantitative studies and between 22 and 58 for qualitative studies. 19 studies were conducted in rural contexts 23,28,29,44,45,53,54,59,60,[66][67][68]73,75,76,81,82,85,86 and 35 in urban and/or peri-urban contexts 22,24,26,31,33,[35][36][37][40][41][42]46,[48][49][50][51][52][55][56][57][58][61][62][63][64][65]69,71,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations